2012
DOI: 10.1590/s0104-11692012000600021
|View full text |Cite
|
Sign up to set email alerts
|

Social representations of needlestick injuries

Abstract: Objectives: understand the Social Representations about needlestick injuries elaborated byNursing Technicians and analyze how these representations influence their conducts. Method: the data, obtained by interviews, were processed using ALCESTE software and their analysis was based on Serge Moscovici's Social Representations Theory. Results: it was evidenced that, after the accident, these professionals take care of the affected area. Then, they report the accident, motivated by the fear of catching HIV and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…A study carried out in a private hospital in the state of Piauí revealed that after occupational exposure with sharps, workers experienced feelings of worry, fear of contracting HIV, hepatitis B or C, and guilt due to the occurrence of the accident. 20 Regarding the number of exposures in the previous year, the majority of these individuals reported one occupational accident with biological material in the period, similar to the individuals with high IES-R scores, however, the variable number of exposures/ year was not compared regarding the IES-R scores. The results of one study 15 showed that professionals with greater numbers of previous experiences of disasters had higher chances of intrusive memories.…”
Section: Ies-r Scoresmentioning
confidence: 95%
“…A study carried out in a private hospital in the state of Piauí revealed that after occupational exposure with sharps, workers experienced feelings of worry, fear of contracting HIV, hepatitis B or C, and guilt due to the occurrence of the accident. 20 Regarding the number of exposures in the previous year, the majority of these individuals reported one occupational accident with biological material in the period, similar to the individuals with high IES-R scores, however, the variable number of exposures/ year was not compared regarding the IES-R scores. The results of one study 15 showed that professionals with greater numbers of previous experiences of disasters had higher chances of intrusive memories.…”
Section: Ies-r Scoresmentioning
confidence: 95%